KINERJA KARYAWAN DITINJAU DARI KEPUASAN KERJA DAN KOMITMEN ORGANISASI - I Made Budiana (POLITEKNIK LP3I JAKARTA, 2023)
Employee performance is very important aspect for every organization. Employee performance is determined as the achievements obtained by employees both qualitatively and quantitatively. The aim of this research is to examine the role of job satisfaction and organizational commitment on the performance of motor vehicle claims employees at PT. CAI. Job satisfaction is the result of employees' thoughts and feelings which describe the importance or unimportance, likes or dislikes of the employee's assessment of their work. Meanwhile, organizational commitment is an individual's interest in the values and goals of the organization. Data was taken from (N=25) motor vehicle claims officers using measuring instruments from Faculty of Psychology, Tarumanagara University. The research results show that job satisfaction does not have a significant effect on performance. Organizational commitment also shows no significant effect on performance. This research is very important to enrich theoretical studies of specific factors that influence employees Keywords: Job Satisfaction, Organizational Commmitment, Employees Performance